Integration of life cycle assessments (LCA) in circular bio-based wall panel design. (10th April 2022) - Cascione, Valeria; Roberts, Matt; Allen, Stephen; Dams, Barrie; Maskell, Daniel; Shea, Andy; Walker, Pete; Emmitt, Stephen
Abstract: To assess the potential benefits and impacts of circular bio-based buildings, life cycle assessment (LCA) is a valuable method to identify systems or elements that have negative effects on the environment during the whole building life. To achieve low carbon buildings, LCA should be performed during the early design stage of buildings, to influence the choice more environmentally led solutions. In this paper, LCA was used during the early design stage of a circular bio-based wall panel prototype to guide the decision-making process for the improvement of the panel's design. A cradle-to-cradle life cycle assessment was performed to compare the circular wall panel against other prefabricated wall panels, assembled using common construction materials and techniques. Results indicated that a circular design and some bio-based materials are not always synonymous with low environmental impacts. The first iteration of the circular panel had a GWP 100 of 231.1 kgCO 2 e/m 2 in the base case with one life cycle. This compared to 116 kgCO 2 e/m 2 and 181 kgCO 2 e/m 2 for the timber and steel frame panels respectively. The LCA was able to identify materials and components which contribute most significantly to the panels environmental impact. The identification of highly impacting materials in the initial panel design, LCA was used to guide the re-design of the circular bio-based panel. From investigating alternative materials for the insulation, cladding and internal substrate the environmental impact of the new design of the circular panel was lowered to 122 kgCO 2 e/m 2 . This research demonstrates how LCA can be used in the design process to reduce carbon emissions in circular buildings by using bio-based materials. Graphical abstract: Highlights: LCA was used to improve sustainability of a prototype of circular bio-based wall. Scenario's development and comparison with common walls help identify hot spots. Circular wall GWP is up to 95% higher than conventional walls (116 and 181 kgCO2 /m 2 ). LCA identified lower impacting materials to reduce GWP of circular bio-based wall. The circular panel GWP was reduced to 122 from 231 kgCO2 /m 2 of the initial design.